Transformation of Early Reading Ability Through Smart Wheel Media Based on the TGT Learning Model - Salsabila Dhia Candra; Sismulyasih, Nugraheti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study introduces the Kintar/Smarwheel learning media, a one meter diameter Smart Wheel media that was developed using the Team Game Tournament (TGT) learning model to improve the initial reading skills of grade 1 elementary school students. The problem of urgency is highlighted by the low reading ability of the average grade 1 child, encouraging the development of effective learning media. This research aims to develop, validate and evaluate the effectiveness of Kintar in improving student learning outcomes in early reading. This study uses a development approach, integrating the product design phase, feasibility validation by media and materials experts, and effectiveness testing through small and large scale trials involving grade 1 students from SDN Purwoyoso 03, Semarang City. Feasibility assessments by experts confirmed a high degree of suitability for educational use, with significant improvements in student learning outcomes observed during the pilot. The small scale trial showed an average increase from pretest to posttest scores from 46.67 to 70.00, with a significant difference of 23.33. The large-scale trial showed a mean increase from 61.47 to 81.47, with a striking difference of 20.00. The N-Gain test results show a moderate impact, with values ​​of 0.3959 and 0.5298 for small and large scale tests, respectively. This study concludes that Kintar, integrated with the TGT learning model, is a powerful educational tool for improving early reading skills. Positive feedback from students and teachers underscores its effectiveness in generating engagement and improving learning outcomes in the classroom.